2010
DOI: 10.1371/journal.pone.0011164
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatomes of the Multicellular Myxobacteria Myxococcus xanthus and Sorangium cellulosum in Comparison with Other Prokaryotic Genomes

Abstract: BackgroundAnalysis of the complete genomes from the multicellular myxobacteria Myxococcus xanthus and Sorangium cellulosum identified the highest number of eukaryotic-like protein kinases (ELKs) compared to all other genomes analyzed. High numbers of protein phosphatases (PPs) could therefore be anticipated, as reversible protein phosphorylation is a major regulation mechanism of fundamental biological processes.MethodologyHere we report an intensive analysis of the phosphatomes of M. xanthus and S. cellulosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…It has also been reported that PP2c-type PPs can compete with ELKs in bacteria [ 37 ]. However, a higher number of PP2c-type PPs has been observed in M. rosea (21 genes) than A. dehalogenans (2 genes), M. xanthus (4 genes), and S. cellulosum So ce56 (16 genes), reported as the highest PP2c-type PPs containing prokaryote [ 38 ]. Moreover, an elevated ratio of ELKs/PPs has been also observed in M. rosea (8.2/1), as in A. dehalogenans (1.7/1), M. xanthus (6.9/1), and S. cellulosum So ce56 (7.7/1) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that PP2c-type PPs can compete with ELKs in bacteria [ 37 ]. However, a higher number of PP2c-type PPs has been observed in M. rosea (21 genes) than A. dehalogenans (2 genes), M. xanthus (4 genes), and S. cellulosum So ce56 (16 genes), reported as the highest PP2c-type PPs containing prokaryote [ 38 ]. Moreover, an elevated ratio of ELKs/PPs has been also observed in M. rosea (8.2/1), as in A. dehalogenans (1.7/1), M. xanthus (6.9/1), and S. cellulosum So ce56 (7.7/1) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a higher number of PP2c-type PPs has been observed in M. rosea (21 genes) than A. dehalogenans (2 genes), M. xanthus (4 genes), and S. cellulosum So ce56 (16 genes), reported as the highest PP2c-type PPs containing prokaryote [ 38 ]. Moreover, an elevated ratio of ELKs/PPs has been also observed in M. rosea (8.2/1), as in A. dehalogenans (1.7/1), M. xanthus (6.9/1), and S. cellulosum So ce56 (7.7/1) [ 38 ]. It could explain the phosphorylation events which cannot be reversed by PPs during multicellular development in myxobacteria [ 38 ] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large numbers of kinases are disproportionate with genome size as a consequence of extensive gene duplication [ 58 ]. As might be expected, the number of genes encoding Ser/Thr phospho-protein phosphatases in myxobacterial genomes correlates with their number of Ser/Thr kinases, but in far smaller numbers [ 59 ].…”
Section: Myxobacterial Genome Biologymentioning
confidence: 93%
“…1) (18). Eight invariant residues in the conserved motifs of PP2C-like protein phosphatases also exist in Pph3 (24,27).…”
mentioning
confidence: 99%